The capital structure of European Multinational Corporations - Gonçalves, Beatriz Carvalho Valente da Mota (2017)
This paper investigates if there are differences in the capital structure of European Multinational Firms and European Domestic Corporations, and if so, which factors can explain the differences. Additionally, this paper also studies whether European Multinational Corporations which have bigger exposure to the European market have different capital structures than European Multinational Corporations which are more exposed to the Global market (market outside Europe). The result shows, as in the U.S., European Multinational Corporations have lower debt rations than European Domestic firms. This difference can be explained by several firm-related factors: non-debt tax shields, profitability, age, foreign exchange risk, size and collateral value. When industry effects are considered, the difference in the level of leverage is not statistically significant. This paper proves that European Multinational Corporations have different capital structures considering the markets which they are exposed. European Multinational Corporations which have higher exposure to the European market have higher leverage ratios due to factors such as profitability, free cash flows available and size. The difference remains even if the industry effects are considered. Finally, the determinants of leverage are also analysed and they vary over the sample period for all firms: Domestic Corporations, Multinational Corporations, Multinational Corporations which are more exposed to the European market and Multinational Corporations which are more exposed to the global market.